2015
DOI: 10.1371/journal.pone.0131391
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Shoots and Roots of TNG67 and TCN1 Rice Seedlings under Cold Stress and Following Subsequent Recovery: Insights into Metabolic Pathways, Phytohormones, and Transcription Factors

Abstract: Cold stress affects rice growth, quality and yield. The investigation of genome-wide gene expression is important for understanding cold stress tolerance in rice. We performed comparative transcriptome analysis of the shoots and roots of 2 rice seedlings (TNG67, cold-tolerant; and TCN1, cold-sensitive) in response to low temperatures and restoration of normal temperatures following cold exposure. TNG67 tolerated cold stress via rapid alterations in gene expression and the re-establishment of homeostasis, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 68 publications
0
50
0
1
Order By: Relevance
“…lipid membranes) [10,12]. Several studies have used transcriptomics to compare cold stress response, however, they focused on closely related taxa or varieties within model species [17,[32][33][34][35][36]. As such, these studies were not able to investigate evolutionary mechanisms underlying adaptation to cold climates of entire clades.…”
Section: Introductionmentioning
confidence: 99%
“…lipid membranes) [10,12]. Several studies have used transcriptomics to compare cold stress response, however, they focused on closely related taxa or varieties within model species [17,[32][33][34][35][36]. As such, these studies were not able to investigate evolutionary mechanisms underlying adaptation to cold climates of entire clades.…”
Section: Introductionmentioning
confidence: 99%
“…This effect of long-term stress is further supported by the fact that bins for regulation of transcription and protein synthesis were enriched for down-regulated genes, while they were enriched for up-regulated genes after a short-term cold stress in the roots of a tolerant rice cultivar (Yang et al, 2015). …”
Section: Discussionmentioning
confidence: 83%
“…However, JA signaling appears to involve a more complex hormonal interaction since JA stimulated the expression of crucial enzymes for ABA biosynthesis, as well as alleviated injury by cold because it also induced cellular alkalinization, which occured through increase in intracellular pH in stomatal guard cells and preceded stomatal closure (Hossain et al 2011). Moreover, in a comparative transcriptome analysis of rice seedlings under cold stress, Yang et al (2015) observed increases in the expression of ABA and JA genes and polyamines, which suggested that a coordinated action established the state of rice cold stress tolerance.…”
Section: Temperature Stressmentioning
confidence: 97%
“…It is not the objective of this review to discuss climate change, although it is a subject that is extremely important, relevant and linked to this sub-section, but it is a subject that is directly linked to plant survival and performance in a changing environment. Low temperatures can reduce enzyme activity by a number of ways, including reduced metabolic rates and operation not in the optimum temperature, hardening of membranes and destabilization of protein complexes, besides the accumulation of ROS, which combined or individually, and depending on the intensity and duration of the stress, may even cause cell death (Gratão et al 2005;Ruelland et al 2009;Yang et al 2015). On the other hand, high temperatures can cause water deficiency in plants by enhancing transpiration and evaporation and change the level and balance of hormone regulation (Nimir et al 2015).…”
Section: Temperature Stressmentioning
confidence: 99%